Redefining the Roles of Aspirin across the Spectrum of Cardiovascular Disease Prevention - Brown, Matthew T.; Bortfeld, Kristina S.; Sperling, Laurence S.; Wenger, Nanette K. (Current Cardiology Reviews, 2023)
Even before its role in platelet inhibition was fully characterized in the 1980s, aspirin had been incorporated into the cardiovascular disease care algorithm. Early trials examining its use in unstable angina and acute myocardial infarction revealed evidence of its protective role in the secondary prevention of atherosclerotic cardiovascular disease (ASCVD). Large trials assessing use in the primary prevention setting and optimal dosing regimens were studied in the late 1990s and early 2000s. As a cornerstone of cardiovascular care, aspirin was incorporated into primary and secondary ASCVD prevention guidelines in the United States and mechanical heart valve guidelines. However, in recent years, with significant advances in medical and interventional ASCVD therapies, scrutiny has been placed on the bleeding profile of aspirin, and guidelines have adapted to new evidence. Updates in primary prevention guidelines reserve aspirin only for patients at higher ASCVD risk and low bleeding risk - though questions remain in ASCVD risk assessment as risk-enhancing factors have proven difficult to incorporate on a population level. New thoughts regarding aspirin use in secondary prevention - especially with the concomitant use of anticoagulants - have altered recommendations as additional data accrued. Finally, a recommendation for aspirin and vitamin K antagonists with mechanical heart valves has been modified. Despite aspirin losing a foothold in cardiovascular care, new evidence has strengthened claims for its use in women at high risk for preeclampsia.
Keywords: atherosclerotic cardiovascular disease